Protecting the environment using the GATT Article XX: chasing shadows - Tapiwa, Shumba (School For Advanced Legal Studies, 2026)
Economic development is at the heart of the World Trade Organisation There is little doubt that trade liberalisation has had some positive effects on the global economy. However, there is considerable agreement on the fact that economic growth may also co me at the expense of environmental protection. To this end, there is also agreement on the need to protect the environment from harmful economic activities such as trade liberalisation which is one of the current multilateral trading system's main instruments for economic growth. The debate on how this can be achieved has been going on for some time and has mainly been around the use of Article XX of the General Agreement on Tariffs and Trade to protect the environment from harmful trade practices. Some piecemeal fashioned suggestions have been made on how to deal with this issue and there has been some hope in many instances that environmental protection will become accommodated within the multilateral trading system. However, as practice has shown, the use of Article XX of the GATT has not, at most, been successful for many reasons. It is these reasons and the solutions to such, which this paper seeks to address, in light of a strong view that the use of the GATT article XX, in its current state, to protect the environment is a futile process and cannot yield positive results.